SmPO4-coated Li1.2Mn0.54Ni0.13Co0.13O2 as a cathode material with enhanced cycling stability for lithium ion batteries. Issue 6 (15th April 2017) - He, Lei; Xu, Junmin; Han, Tao; Han, Hui; Wang, Yongjian; Yang, Jun; Wang, Jingrong; Zhu, Wenka; Zhang, Changjin; Zhang, Yuheng
Abstract: SmPO4 coated Li1.2 Mn0.54 Ni0.13 Co0.13 O2 cathode materials were prepared by the precipitation method and calcined at 450 °C. The crystal structures and electrochemical properties of the pristine and coated samples are studied by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, electron diffraction spectroscopy, galvanostatic cycling, cyclic voltammetry, and electrochemical impedance spectroscopy (EIS). It has been found that the electrochemical performances of the Li-rich cathode material have been substantially improved by SmPO4 surface coating. Especially, the 2 wt% SmPO4 -coated sample demonstrates the best cycling performance, with capacity retention of 88.4% at 1 C rate after 100 cycles, which is much better than that of 72.3% in the pristine sample. The improved electrochemical properties have been ascribed to the SmPO4 coating layer, which not only stabilizes the cathode structure by decreasing the loss of oxygen, but also protects the Li-rich cathode material from side reaction with the electrolyte and increases the Li + migration rate at the cathode interface.